Classification of Breast Tissue for Mammograms Images Using IntensityHistogram and Statistical Methods - Hussain, Alyaa; Mazher, Alaa; Razak, Asraa (Iraqi Journal of Science, 2024)
In order to classify a image texture it must be segmented into a number ofregions. each region have the same properties. a circular mask has been used. afterthe required region is obtained a intensity histogram and then as set of histogramfeatures has been calculated in order to classify the required images.The statistical features of a mammogram are extracted using image processingtechniques. The extracted statistical features are the mean, standard deviation,smoothness, third moment uniformity and entropy for each of the histogramintensity and first order statistic a compare between the two